Emerging roles for tRNAs in hematopoiesis and hematological malignancies. Issue 6 (June 2022) - Lee, Anna K.; Aifantis, Iannis; Thandapani, Palaniraja
Abstract : tRNAs are central players in decoding the genetic code linking codons in mRNAs with cognate amino acids during protein synthesis. Recent discoveries have placed tRNAs as key regulators of gene expression during hematopoiesis, especially in hematopoietic stem cell (HSC) maintenance and immune development. These functions have been shown to be influenced by dynamic changes in tRNA expression, post-transcriptional base modifications, tRNA-interacting proteins, and tRNA fragmentation; these events underlie the complexity of tRNA-mediated regulatory events in hematopoiesis. In this review, we discuss these recent findings and highlight how deregulation of tRNA biogenesis can contribute to hematological malignancies. Highlights: tRNA biogenesis is emerging as an important regulator of human hematopoiesis and immune function. tRNA expression signatures mirror the codon bias of the transcriptome during development of mouse immune cells (CD4 + T cells), coordinating demands of cell type-specific mRNA translation. tRNAs are targets of ribonucleases generating a wide array of tRNA microspecies that act as both cell intrinsic and extrinsic signaling molecules regulating hematopoiesis and immune functions in humans and mouse. Deregulation of tRNA biogenesis can contribute to the pathogenesis of hematological malignancies, offering a new avenue for potential therapeutic intervention in humans.